Language and gender - Eckert, Penelope, 1942-; McConnell-Ginet, Sally (Cambridge University Press, 2013)
"Language and Gender is an introduction to the study of the relation between gender and language use, written by two leading experts in the field. This new edition, thoroughly updated and restructured, brings out more strongly an emphasis on practice and change, while retaining the broad scope of its predecessor and its accessible introductions which explain the key concepts in a non-technical way. The authors integrate issues of sexuality more thoroughly into the discussion, exploring more diverse gendered and sexual identities and practices. The core emphasis is on change, both in linguistic resources and their use and in gender and sexual ideologies and personae. This book explores how change often involves conflict and competing norms, both social and linguistic. Drawing on their own extensive research, as well as other key literature, the authors argue that the connections between language and gender are deep yet fluid, and arise in social practice"--Resumé vydavatele
Keywords: gender; sociolingvistika; jazyk; sociolinguistics; language; monografie; monographs